Behind the Mask: A Psychological Exploration of Emily Nelson’s Sociopathic Traits in A Simple Favor Movie - Astuti, Theresia Mundi; Sauomi, Hema; Prasatyo, Bayu Andika (JETAL: Journal of English Teaching & Applied Linguistic, 2025)
This study aims to showcase the personality disorder of a single character in “A Simple Favor” movie. Applying a qualitative method, the researchers employ a descriptive qualitative method to examine the characteristic type of the main character’s sociopathic personality disorder. The findings reveal that the main character named Emily Nelson exhibits a complicated sociopathic personality disorder defined by three interconnected dimensions: narcissistic, amoral, and aggressive characteristics traits of a sociopath. Emily's narcissism is shown by her arrogance, entitlement, and deceptive behavior. Her amoral behavior indicates a serious absence of guilt for her detrimental deeds. The latter sociopathic characteristic she displays is aggressiveness. Emily’s aggression is purely utilitarian and expressive. The study highlights the utility of psychological frameworks in analyzing fictional characters, enriching literary and film criticism by providing deeper insight into character motivation and complexity. The recommendation include analyzing a broader range of characters across different films or literary works to identify common patterns and unique features in the depiction of sociopathy. Besides that, comparative studies would enhance understanding of how antisocial personality disorder is represented in popular culture. The study exclusively analyzes the character Emily Nelson from “A Simple Favor” movie, focusing on her sociopathic traits as depicted in a fictional narrative. This limits the generalizability of findings to real-life cases of sociopathy or antisocial personality disorder, as film characters are constructed for dramatic effect and may not fully align with clinical realities